Surgical Margins in Soft Tissue Sarcoma Management and Corresponding Local and Systemic Recurrence Rates: A Retrospective Study Covering 11 Years and 169 Patients in a Single Institution - Silvan Wittenberg; Melissa Paraskevaidis; Armin Jarosch; Anne Flörcken; Franziska Brandes; Jana Striefler; David Kaul; Siyer Roohani; Thilo Khakzad; Sven Märdian; Daniel Rau (Life, 2022)
Soft tissue sarcomas (STSs) are a diverse group of rare malignant soft tissue tumors with a high disease burden. Treatment protocols are complex and, to this day, a precise recommendation for the surgical margin width is lacking. The present study aims to analyze the width of the surgical margins in STS resection specimens and analyze them for local and systemic disease-free survival as well as for most frequent histologic STS subtypes. A total of 169 consecutive patients diagnosed and treated in curative intent in our institution following a primary and localized STS of the extremities or trunk from January 2010 to December 2020 were included in this study regardless of age. Our data reveal that low-grade STSs are best controlled locally by a surgical margin ≥2 mm and in this way also preventing distant metastases effectively. Local recurrence-free survival and metastasis-free survival in high-grade STS were improved by intact muscle fascia or periosteum at the margin when compared only to soft tissue. However, the outcome was independent of the surgical margin width, suggesting a close but negative margin may be safe in high-grade STS subtypes with less invasive growth patterns when combined with adjunct radiochemotherapy.